Policing the Police: The Role of the Courts and the Prosecution - Zeidman, Steven (2005)
This Article focuses on how, and whether, the component parts of the courts - judges, court administrators, and prosecutors - promote justice by actively and critically monitoring or overseeing the police. The author focuses on one of the most common forms of police corruption facing the criminal justice system - what has been termed falsifications which includes testimonial perjury, documentary perjury and falsification of police records. The author reflects on what judges and prosecutors have done to combat this form of police corruption and offers ways in which the actors within the criminal justice system can be more effective